The polytraumatized in the interior of the country. Communication of the Paso Pache experience - González, Daniel; Vega, Alvaro; Monti, José; Torres, Marcos; di Leoni, Francisco (Cirugía del Uruguay, 2005)
Po/itraumatism, one of the main causes of morbimortality in current days, and one which affects mainly people in ful/ productive activity, requires for its care trained personnel as we/1 as an adequate infrastructure. A review of that which has historical/y occurred away from main centers, shows that at the onset and middle of the XX century, main etio/ogfc agents were wounds caused by blades and firearms together with closed traumatisms caused by horse kicks. This state of affairs started to change during the seventies, when traffic accidents become foremost